Neuronal nitric oxide synthase required for erythropoietin modulation of heart function in mice - Lee, Jeeyoung; Rogers, Heather M.; Springer, Danielle A.; Noguchi, Constance T. (Frontiers in Physiology, 2024)
Erythropoietin (EPO) is the primary regulator of erythropoiesis although EPOR expression extends beyond erythroid tissue, providing for non-hematopoietic EPO response. In animal models, nitric oxide (NO) synthase (NOS) and NO production contributes to EPO activity including erythropoiesis and neuro-and cardio-protection. However, high dose EPO treatment in patients with chronic kidney disease was linked to increased risk of serious cardiovascular events and mortality. We found that while heart function in mice is protected by endogenous EPO, heart function is impaired by prolonged EPO treatment to increase hematocrit. Impaired heart function by EPO treatment is independent of EPO stimulated erythropoiesis and requires EPOR in nonerythroid tissue. Increases in expression of heart failure-associated genes were consistent with decreased heart function. While nNOS-/-mice show increased hematocrit with EPO treatment, albeit with a trend toward lower hematocrit compared with wild type mice, nNOS-/-mice are protected from the adverse effect of EPO treatment on heart function. These findings reveal the potential for high dose EPO treatment to compromise heart function independent of increased hematocrit and the contribution of NOS activity to both the beneficial and adverse effects of EPO and raise the potential for a role for protein S-nitrosylation in EPO activity.